2017
DOI: 10.1002/jmri.25904
|View full text |Cite
|
Sign up to set email alerts
|

Breast lesion characterization using whole‐lesion histogram analysis with stretched‐exponential diffusion model

Abstract: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1701-1710.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 33 publications
(67 reference statements)
2
40
0
Order By: Relevance
“…K min , D max , and ADC max were precisely representative of the most unrestricted diffusion of necrosis, so they did not show any differences between benign and malignant lesions. Kurtosis and skewness are metrics that describe the distribution pattern of parameters, and the result indicated that there was no difference in the distribution pattern of parameters between the benign and malignant groups, which is consistent with a previous study of histogram analysis with the stretched‐exponential model . Furthermore, ADC histogram parameters (from ADC min to ADC sd ) were significantly lower than D histogram parameters (from D min to D sd ) in benign and malignant lesions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…K min , D max , and ADC max were precisely representative of the most unrestricted diffusion of necrosis, so they did not show any differences between benign and malignant lesions. Kurtosis and skewness are metrics that describe the distribution pattern of parameters, and the result indicated that there was no difference in the distribution pattern of parameters between the benign and malignant groups, which is consistent with a previous study of histogram analysis with the stretched‐exponential model . Furthermore, ADC histogram parameters (from ADC min to ADC sd ) were significantly lower than D histogram parameters (from D min to D sd ) in benign and malignant lesions.…”
Section: Discussionsupporting
confidence: 89%
“…K max , D min , and ADC min had significantly higher sensitivity than their individual mean value, while specificity did not differ significantly. In a previous study of ADC histogram parameters, Liu et al found that ADC 10 yielded the highest AUC (0.893) for differentiating malignant from benign lesions. Suo et al demonstrated that the AUC of ADC min and ADC 25 were both significantly higher than that of ADC mean .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…some studies demonstrated the utility of bi-exponential model for differentiating benign and malignant tissues. [5][6][7][8] However, tumor tissue and its microstructure are complex and varied, and it can be less than ideal to characterize them using only two intravoxel proton pools, as in the bi-exponential model. To overcome this limitation of bi-exponential models, a stretched exponential model has been introduced.…”
Section: Introductionmentioning
confidence: 99%
“…This model enables the measurement of the water diffusion heterogeneity index α, which ranges from 0 to 1 (a value of 1 indicates water diffusion). Accumulating evidence suggests that stretched-exponential DWI is useful for assessing gliomas [11][12][13][14][15][16] and other tumors, including breast [17], pancreatic [18], hepatic [19], prostate [20], bladder [21], and renal cancers [22].…”
Section: Introductionmentioning
confidence: 99%